Life-history and stock assessment of Clarias Gariepinus in the Okavango Delta, Botswana - Bokhutlo, Thethela (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2012)
Large catfishes (Clarias gariepinus & Clarias ngamensis) are not exploited commercially in the Okavango Delta, Botswana. They however constitute a large proportion of the gill net fishery catch (23 %) albeit as by-catch, coming second after cichlids (70 %). Monthly experimetal gill net sampling over 8 years showed that C. gariepinus was the most abundant species in the Okavango Delta by mass making up 37 % of the catch composition by fresh weight. Despite the relatively high abundance of C. gariepinus in the Okavango Delta, its status has never been fully assessed. For this reason, this study aimed to assess the status of C. gariepinus in the Okavango Delta with the particular goal to determine if the species could support a directed commercial gill net fishery. Investigation of the effects of the flood pulse on abundance of C. gariepinus showed that variability in water levels was the major driver of population abundance for this species. Three biological variables: (1) catch per unit effort (CPUE); (2) % catch composition and (3) Shannon's diversity index (H') exhibited a negative and significant relationship with the flood index within a year. The variation in these variables was statistically significant between months. There was a weak positive relationship between water levels and the biological variables between years suggesting increase in productivity of the system at high water levels without a lag period. Age and growth were determined using sectioned otoliths. Edge analysis showed that growth zone deposition occurred during the drawdown period in summer when water temperature and day length were increasing. The maximum recorded age was 15 years. Growth of this species was best described by the linear models (y = 21.50x + 427.39 mm LT; rÂ² = 0.35) for females and (y = 23.79x + 440.83 mm LT; rÂ² = 0.38) for males. The von Bertalanffy growth model described growth as Lt = 10000(1- exp(-0.002(t + 18.07))) mm LT for combined sexes Lt = 10000(1- exp( -0.002(t + 18.50))) mm LT , for females and Lt =908(1-exp(-0.076(t+7.95)))mmLT for males. Age at 50 % maturity was attained in the first year of life. Spawning occurred throughout the year with an apparent peak between November and April. The mean total annual mortality rate (Z) was 0.25 per year. The mean annual natural mortality rate (M) was 0.20 per year and fishing mortality (F) was calculated at 0.05 per year. The life history strategy of C. gariepinus was in between the periodic and opportunistic strategies. Therefore management of this species should be aimed at maintaining a healthy adult population and age structure. Since a large portion of the Okavango Delta is already protected and most other parts are also inaccessible to fishers there are enough spatial refugia for the species and the status quo should be maintained. Under this scenario, there is no need for regulation of the current mesh sizes because the species is harvested after maturity and replenishment of exploited populations will always occur from other parts of the system. Per recruit analyses indicate that the current fishing mortality maintains spawner biomass at levels greater than 90 % of pristine levels. Therefore a commercial fishery may be established using mesh 93 mm to maximize yield with a rotational harvesting strategy. Close monitoring is essential to ensure that re-colonization of overexploited habitats does indeed occur. Recreational angling and commercial gill net fishing need to be separated on a spatial and temporal scale during the feeding run to minimize potential conflicts.
Keywords: Catfishes -- Botswana -- Okavango River Delta; Clarias gariepinus; Aquaculture -- Botswana -- Okavango River Delta